Legal Education in Malaysia in the Context of Legal Practice - Mohamad Ali, Norfadhilah; Hazmi Mohd Rusli, Mohd; Abdul Shukor, Syahirah; Nasir Abdul Majid, Mohd; Abd Rahman Shah, Hendun; Zaki Salleh, Ahmad; Abdul Mutalib, Lukman; ., Al’Uyuna; Amin, Mohd; Md Nor, Marsita (International Journal of Engineering and Technology, 2018)
Upon attaining independence in 1957, most judges and lawyers in Malaysia received legal education and legal training in the United Kingdom. University of Malaya was the only premier law school in Malaysia during that time. Gradually, the number of law schools increased and now legal education is available in a number of both private and public universities in Malaysia. The landscape of legal education differ post 2008 when new law schools from public universities were made subject to a review conducted by the Legal Profession Qualifying Board (LPQB) â€“ failure to obtain full recognition will result in students from the universities concerned, having to sit for Certificate in Legal Practice (CLP) examination. In the light of this development, legal education in Malaysia has become under strict Â scrutiny by the legal fraternity, and thus it is a question of what reasonable expectation should the country set on the legal education provided by universities. This article will address legal education from the point of view of universities, the relevance of the CLP examination and the level of skills and knowledge required to produce â€˜practice-readyâ€™ graduates. The discussion also considers the availability of the 9-months pupillage before admission to the Malaysian Bar and Â other criteria for education as provided for by the Malaysian Qualifications Agency (MQA). The whole paper will be based on the Â Legal Profession Act 1976, the MQA guidelines, the developments of legal education in Malaysia and the experience of laws schools under review by the LPQB and other stakeholders.Â Â Â